Prevalence of dental caries and fissure sealants in a portuguese sample of adolescents - Veiga, Nélio J. (2015)
Introduction: The aims of this study were to assess the prevalence of dental caries and the DMFT index, as well as the distribution pattern of pit and fissure sealants on permanent teeth in a Portuguese sample of adolescents, and to assess whether the existing usage of sealants and socio-demographic factors are correlated to caries prevalence on the examined sample. Materials and Methods: A cross-sectional study was designed with a sample of 447 adolescents aged 12 to 18 years old, attending a public school in Sátão, Portugal. A self-administered questionnaire with questions about oral health behaviours and socio-economic status was answered by adolescents in the classroom. Clinical examination of oral health status and assessment of fissure sealants were accomplished by only one trained member of the research team. Results: We obtained a DMFT index of 3.32 (2.92), which indicates a moderate level of prevalence of dental caries. When considering a DMFT=0, we found significant statistical differences between the parents´ level of education (≤ 4th grade=26.3 vs 5th-12th grade=18.8 vs >12th grade=43.3, p=0.001), gender (male=27.3 vs female=19.6, p=0.04), age (≤15 years=27.1 vs >15 years=18.5, p=0.02), presence of fissure sealants (yes=30.6 vs no=13.5, p=0.001) and experience of dental pain (no=25.4 vs yes=16.8, p=0.02). When analyzing the prevalence of fissure sealants, we verified that 58.8% of adolescents had at least one fissure sealant applied. Significant statistical differences were found when analyzing the presence of fissure sealants related with parents´educational level (>9th grade, OR=1.56 CI95%=1.05-2.54), gender (female, OR=1.86 CI95%=1.19-2.98), experience of dental pain (yes, OR=0.62 CI95%=0.39-0.97) and presence of dental caries (yes, OR=0.35 CI95%=0.19-0.65). Conclusions: The moderate level of caries prevalence reveals the need of improvement of primary prevention interventions among Portuguese adolescents. The establishment of a more targeted preventive program with better and more effective oral health education is essential, having into account socio-demographic aspects.